Immunohistochemical subtypes predict the clinical outcome in high-risk node-negative breast cancer patients treated with adjuvant FEC regimen: results of a single-center retrospective study. Issue 1 (December 2015) - Rahal, S.; Boher, J; Extra, J; Tarpin, C.; Charafe-Jauffret, E.; Lambaudie, E.; Sabatier, R.; Thomassin-Piana, J.; Tallet, A.; Resbeut, M.; Houvenaeghel, G.; Laborde, L.; et al.
Abstract Background Anthracycline-based adjuvant chemotherapy improves survival in patients with high-risk node-negative breast cancer (BC). In this setting, prognostic factors predicting for treatment failure might help selecting among the different available cytotoxic combinations. Methods Between 1998 and 2008, 757 consecutive patients with node-negative BC treated in our institution with adjuvant FEC (5FU, epirubicin, cyclophosphamide) chemotherapy were identified. Data collection included demographic, clinico-pathological characteristics and treatment information. Molecular subtypes were derived from estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2) status and Scarff-Bloom-Richardson (SBR) grade. Disease-free survival (DFS), distant disease-free survival (DDFS) and overall survival (OS) were estimated using the Kaplan-Meier Method, and prognostic factors were examined by multivariate Cox analysis. Results After a median follow-up of 70 months, the 5-year DFS, DDFS and OS were 90.6 % (95 % confidence interval (CI): 88.2–93.1), 92.8 % (95 % CI: 90.7–95) and 95.1 % (95 % CI, 93.3–96.9), respectively. In the multivariate analysis including classical clinico-pathological parameters, only grade 3 maintained a significant and independent adverse prognostic impact. In an alternative multivariate model where ER, PR and grade were replaced by molecular subtypes, only luminal B/HER2-negative and triple-negative subtypes were associated with reduced DFS and DDFS. Conclusions Node-negative BC patients receiving adjuvant FEC regimen have a favorable outcome. Luminal B/HER2-negative and triple-negative subtypes identify patients with a higher risk of treatment failure, which might warrant more aggressive systemic treatment.